Estimation of Capacity and Center of Weight of Traditional Ship, Bagan Siapiapi - Badri, Muftil; Damanik, Pindo Evans Manuel; Yohanes, Yohanes (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
On traditional manufactures fishing boats in Indonesia, especially in the shipyard at Bagan Siapiapi, on Riau province usually made by rely on the ability of inherited tradition and hereditary not based on function and their designation. Example that way still used when determine capacity and center of gravity. This research aims to study capacity and center gravity of ship nets at Bagan Siapiapi using computer simulations. On this method some of data about capacity, center of gravity, drawing design and construction of ships would to be studied systematic and accurate base on practical condition. That case would be studied and validate on the one shipyard industry at Bagan Siapiapi. Some result from this study are (1) Capacity of ship nets 7093 kg and the weight is 13401.04 kg on the full condition. (2) Center weight of ship nets at X = 0.7mm; Y = 888.5mm; and Z = -162.5 mm. (3) Stability of ship nets on the without load has a smaller tilt angle compare than the full load condition.